A giant retroperitoneal liposarcoma encasing vital organs: A case report - Adeena Azam; Mufti, Amna Faheem; Faizan Masood; Hafiz Usman Azeem (Journal of the Pakistan Medical Association, 2025)
Liposarcoma is the most common primary malignant tumour of the retroperitoneum. As the retroperitoneum is a large space, these tumours can grow significantly before diagnosis. In this case, a 67-year-old male was admitted to a hospital with the complaint of weight loss and abdominal distension. A palpable mass was detected on physical examination, the A scan of this showed it to be retroperitoneal, heterogenous, with multiple septations, calcifications and solid components. It was removed successfully via midline incision. Liposarcoma is derived from adipose tissue and is a soft tissue sarcoma. In most cases, retroperitoneal liposarcoma presents as a painless mass, evident on physical examination. These tumours can go undetected for long periods, as symptoms usually arise only when the mass becomes significantly large. Symptoms include abdominal pain and constipation. Surgical resection is the mainstay of treatment for liposarcoma. Special care must be taken to preserve abdominal organs, which may be difficult considering the size of the mass, especially in resource-limited environments. Keywords: Liposarcoma, retroperitoneal liposarcoma.